Early discharge and rehabilitation in paediatric acquired brain and neurological injury: a transferable model. Issue 1 (20th October 2018) - Keetley, Rachel; Kelly, Laura; Whitehouse, William P; Thomas, Sophie; Bennett, Emily; Chow, Gabriel; Fletcher, Alison; Williams, Jane
Abstract : Children and young people who require rehabilitation following sustaining an acquired brain injury often experience long lengths of stay (LOS) and potentially poorer recovery outcomes due to limited access to therapy and little proactive discharge planning. After stakeholder enquiry we launched a new team and pathway with a primary aim to reduce LOS. The secondary aims were to pilot an outreach model, reduce cost and improve patient and family satisfaction. We achieved a significantly improved change in quality care with a financial gain and increased patient and family satisfaction.